Mid- and Longer-term Follow up of Chimney and/or Periscope Grafts and Risk Factors for Failure. Issue 5 (May 2016) - Pecoraro, F.; Veith, F.J.; Puippe, G.; Amman-Vesti, B.; Bettex, D.; Rancic, Z.; Pfammatter, T.; Lachat, M.
Abstract : Objective: The aim was to report on chimney and periscope grafts (CPGs) and their mid- and longer-term outcomes when they are used to preserve reno-visceral artery (RVA) perfusion in endovascular repair of pararenal (PRAAs) or thoraco-abdominal aortic aneurysm (TAAAs). In addition, factors associated with CPG failure are presented. Limited data exist on the outcomes of CPGs, and mid- and long-term results are generally not reported. Methods: This was a prospective study in a cohort of 100 patients with PRAA (69) or TAAA (31). A total of 224 (mean 2.24 per patient) RVAs were preserved with 136 (61%) chimney and 88 (39%) periscope grafts. CPGs were constructed mainly using self expandable stent grafts. Patients were followed by clinical examination, CTA (82%), and/or duplex (18%). Data were collected until February 2015. Results: CPG immediate technical success was 99% (222/224 branches). Mean follow up was 29 months (range 0–65; SD 17); 59% patients were followed > 2 years, 30% > 3 years, and 16% > 4 years. Post-operatively, CPG occlusion was observed early (≤30 days) in three (1.3%) branches and during follow up in 10 (4.5%). At 36 and 48 months, the estimated primary patency was 93% and 93%. After corrective percutaneous (10) or surgical (3) re-interventions, the estimated secondary patency was 96% and 96%. Thirty day mortality was 2%; at 36 and 48 months the estimated patient survival was 79%. Significant shrinkage (72 [SD 23] vs. 62 [SD 24] mm; p <  .001) was observed, with a substantial reduction (>5 mm) in 55 patients, and sac enlargement in four. Incomplete aneurysm sac sealing was treated successfully by a secondary intervention in 15 patients. Conclusions: Self expandable CPGs have proved to be a highly successful and durable treatment for RVA preservation up to 5 years. Incomplete CPG expansion, inadequate length, and CPG use in small and diseased target arteries were risk factors for occlusion. These mid- and longer-term results support CPG use to treat PRAAs or TAAAs in patients unfit for open surgery or fenestrated/branched stent grafts.